Behavioural and isotope ecology of marine-foraging chacma baboons (Papio ursinus) on the Cape Peninsula, South Africa - Lewis, Matthew Charles (University of Cape Town, 2015)
The dominant vegetation type on the Cape Peninsula, South Africa, is an oligotrophic shrub land that supports low numbers of medium-sized and large terrestrial mammals. Of these, only the adaptable and dextrous chacma baboon (Papio ursinus) has learnt to supplement its diet with protein-rich foods from the marine intertidal zone. There are qualitative descriptions of this behaviour in the literature, but the relative contribution of marine foods to baboon diet, the influence of lunar cycles on exploitation and the impacts of marine foraging on ranging behaviour and activity budgets through different seasons have yet to be quantified. Furthermore, all previous studies included data from troops that had access to nutrient-rich exotic foods, which may have reduced their reliance on marine organisms. For this thesis I collected behavioural data on ranging patterns, activity budgets and diet of a free-ranging, natural-foraging troop through full lunar tidal cycles over consecutive seasons. I supplemented the behavioural data with estimates of the troop's diet composition modelled from stable isotope ratios of foods, faeces and hair samples. The troop ranged over 45.262km2 and travelled an average of 6.044 km per day over the study period. The troop's activity budget was dominated by walking and feeding behaviour, both of which peaked during the hot, dry summer months. Both spatial and behavioural data suggest that the study troop is nutrient-stressed relative to other troops in this population, and hence it was surprising that they only consumed small amounts of marine foods during all four seasons. Models incorporating δ13C and δ15N values of baboon faeces and hair confirmed that marine foods were not major dietary items for these baboons, whilst generalized additive models revealed that a range of abiotic factors negatively affect the exploitation of marine foods. Both the probability and intensity of marine foraging within a given hour declined with increasing tide height and swell height, and fluctuated depending on wind speed and direction. Intensity of marine foraging varied through seasons (it was highest in autumn and lowest in spring), and was higher on the east coast than on the west. Together, these results suggest that exploitation of nutrient-rich foods in the intertidal zone is limited by rapid, unpredictable changes inaccessibility. The levels of deviance left unexplained by these models however imply that other as yet unknown factors (e.g. alkaloids in mussels and limpets) may also limit the troop's exploitation of marine foods. In conclusion, this thesis represents the first in-depth study of marine foraging, a behaviour which exemplifies baboons' remarkable behavioural and dietary flexibility. That said, the temporal unpredictability of ease of access, and potential dangers associated with harvesting this resource, appear to limit how much of this high nutrient food resource baboons are able utilise.